Comparative study of oxidants in gold cyanidation: A molecular picture. (November 2022) - Nourmohamadi, Hossein; Rezai, Bahram
Highlights: Positive effect of H 2 O 2 and F e ( O H ) 4 - on reaction of C N - over the 111 surface of Au. Stronger interaction of oxygen on the surface of 111 by increasing temperature. Increased nucleophilic properties of surface in the presence of H 2 O 2 . Abstract: Oxygen plays a crucial role in the oxidation of gold in cyanidation. However, gold can be dissolved in oxygen free solutions by other oxidants. Here, the oxidizing potential of two other oxidants including peroxide ( H 2 O 2 ) and iron hydroxide ( F e ( O H ) 4 - ) as the dominant Fe specie in alkaline cyanide solutions has been compared with oxygen. For this purpose, a computational modelling method using DFT has been used with BLYP functional. The interaction energy of O 2, H 2 O 2 and F e ( O H ) 4 - with the 111 surface of Au is calculated and compared in absence and presence of cyanide ion. Oxygen adsorption energy was higher than the other species with energy values of −50. The H 2 O 2 and the F e ( O H ) 4 -, like oxygen, had a positive effect on the interaction of cyanide with 111 surface as well.